2002
DOI: 10.1046/j.1365-2613.2002.00223.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term evolution of the acute tubular necrosis (ATN) induced by glycerol: role of myofibroblasts and macrophages

Abstract: Summary. Late structural changes such as interstitial fibrosis in the renal cortex and tubular atrophy have been detected after severe acute tubular necrosis (ATN). The aim of this study was to investigate the expression of fibronectin, a-smooth muscle actin and macrophages during the evolution of the ATN induced by glycerol and their relationship with the late structural changes observed in the kidneys of these animals. Forty-nine male Wistar rats were injected with a 50% glycerol solution, 8 mL/kg (4 mL/kg a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 26 publications
4
22
0
4
Order By: Relevance
“…In our setting, injection of glycerol induced significant increases in serum BUN, which peaked at day 3, declined at day 7, and stabilized at days 11 and 14 to values that were significantly higher than those in healthy mice ( Figure 9, A and B), as described previously (34,35). Intravenous injection of CD24 ϩ CD133 ϩ PEC on days 3…”
Section: Effects Of Cd24 ϩ Cd133 ϩ Pec On Renal Function and Structuresupporting
confidence: 86%
“…In our setting, injection of glycerol induced significant increases in serum BUN, which peaked at day 3, declined at day 7, and stabilized at days 11 and 14 to values that were significantly higher than those in healthy mice ( Figure 9, A and B), as described previously (34,35). Intravenous injection of CD24 ϩ CD133 ϩ PEC on days 3…”
Section: Effects Of Cd24 ϩ Cd133 ϩ Pec On Renal Function and Structuresupporting
confidence: 86%
“…The proinflammatory response is an important mechanism in the initiation and maintenance of Gly-induced AKI [9,22]. Previous studies reported peak inflammation at 3-5 days after Gly injection [23,24]. In our study, macrophage numbers in kidneys of Gly-treated mice peaked at 24 h. Therefore, early depletion of macrophages by LEC treatment was associated with reduced inflammation in Gly-induced renal injury.…”
Section: Discussionsupporting
confidence: 64%
“…Also in different experimental models, as ischemia, gentamicin, or glycerol, interstitial fibrosis can progress even after functional recovery. [7,14,15] When renal biopsy is performed in native kidney ARF, the histological findings mirror the consequence of an acute injury as tubular necrosis and the response to this acute injury, such as cellular regeneration, inflammatory infiltrate, progressive fibrosis, or loss of glomeruli; however, they also mirror chronic features (present before ARF) such as sclerosed glomeruli and atherosclerotic vascular alterations. Thus, the finding of more intense histological abnormalities in the group with partial recovery represents the result of more severe ARF but also of aging, chronic hypertension, etc.…”
Section: Discussionmentioning
confidence: 99%
“…[5] Other experimental stud-ies of ARF have also shown that chronic structural changes may be observed after the acute injury. [6,7] In the 1970s, Striker et al pointed to the association between interstitial disease and decline of GFR. [8] A more recent study on ATN after renal transplantation showed that patients who had progressed to chronic renal failure presented larger fractional interstitial area in their biopsies than patients with good outcome (34% versus 19%, p < 0.01).…”
Section: Introductionmentioning
confidence: 99%